Dry Cupping Therapy in Overcoming Migraine at Ashadique Healthy Care Clinic Palembang City - Ramadani, Deri Nur; Hakim, Lukman Nul; Septiana, R.A Erika (Program Studi Tasawuf dan Psikoterapi, 2023)
The development of advanced science and technology as well as the increasing standard and quality of human life have made lifestyles irregular and increased working hours. The consequences can have a positive impact on productivity but also produce negative impacts that can be detrimental to physical and psychological health. Migraine is one of the most common headache disorders, characterized by a lateral, intense, throbbing, or throbbing sensation in the head. Cupping is a method of treating thibbun nabawi or treatment suggested by Rasulullah SAW by removing toxins or elements that are not needed in the body. This type of research is a qualitative field research (field research) which obtains data from the field or research site through observation, interviews and dry cupping therapy on patients at the Ashadique Healthy Care Clinic in Palembang City, then the data is analyzed through descriptive analysis. The formulation of this research is How does dry cupping therapy affect Migraine at the Ashadique Healthy Care Clinic in Palembang City, and the purpose of this study is to examine the effect of dry cupping therapy on Migraine at the Ashadique Healthy Care Clinic in Palembang City. The results of this study indicate that, in the two stages of this initial study, the results of dry cupping therapy were carried out, patients felt comfortable in the body being cupped, and improved blood circulation and felt migraines were reduced. In stage three, this was the final result of cupping therapy. dry treatment, in this stage the patient no longer feels migraines like before the therapy was carried out, so that the patient is said to be cured at the end of this cupping therapy method and normal blood circulation